2019
DOI: 10.1161/circinterventions.119.008231
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Trials and Administrative Claims to Identify Stroke Among Patients Undergoing Aortic Valve Replacement

Abstract: Background: Cerebrovascular events (CVEs) are devastating complications after aortic valve replacement. We assessed whether billing claims accurately identify CVEs in place of clinical event adjudication in structural heart disease trials. Methods: Adult participants in the US CoreValve High Risk and SURTAVI trials (Surgical or Transcatheter Aortic-Valve Replacement in Intermediate-Risk Patients) were linked to Medicare inpatient claims f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Despite the rigorous audit by the TVT Registry, there could also be a potential misrepresentation of stroke rates based on the site difference that may have contributed to the different stroke rates. Additionally, the use of administrative claims-based codes for stroke assessment at 1 year appears to have low sensitivity but high specificity, 32 which could potentially misrepresent the stroke rates. Finally, without comparative data on the individual heart team’s nuanced assessment of patient’s surgical risk or the fact that ≈20% of all alternative access patients were not included in the analyses because linkage with CMS was not successful, our findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the rigorous audit by the TVT Registry, there could also be a potential misrepresentation of stroke rates based on the site difference that may have contributed to the different stroke rates. Additionally, the use of administrative claims-based codes for stroke assessment at 1 year appears to have low sensitivity but high specificity, 32 which could potentially misrepresent the stroke rates. Finally, without comparative data on the individual heart team’s nuanced assessment of patient’s surgical risk or the fact that ≈20% of all alternative access patients were not included in the analyses because linkage with CMS was not successful, our findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rigorous audit by the TVT Registry, there could also be a potential misrepresentation of stroke rates based on the site difference that may have contributed to the different stroke rates. Additionally, the use of administrative claims-based codes for stroke assessment at 1 year appears to have low sensitivity but high specificity, 32 which could potentially misrepresent the stroke rates.…”
Section: Limitationsmentioning
confidence: 99%
“…Hay et al successfully demonstrated the feasibility of linking RCT data to administrative data in Canada with a linkage rate of 90.8% [ 10 ]. Another study by Strom et al achieved a match rate of 79.8% by linking clinical trial data to Medicare inpatient discharge data [ 11 ]. Brennan et al linked Medicare claims data to the clinical data from seven randomized cardiovascular trials and achieved a linkage rate of 55.6% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have linked RCT data to administrative claims data with linkage rates ranging from 55.6 to 90.8% [ 10 12 ]. Strom et al [ 11 ] assessed the accuracy of identifying cardiovascular events through billing claims in place of clinical event adjudication in structural heart disease trials by linking clinical trial data to inpatient Medicare claims. Their results indicated that claims could be used to trigger evaluation of neurological events, potentially improving the efficiency of the evaluation of techniques and devices designed to reduce such events.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were linked with indirect identifiers using deterministic matching algorithms based on age, sex, procedure date and type, discharge date, and hospital identifiers as previously described. [9][10][11] We excluded patients who could not be linked to MedPAR files, which included those patients <65 years of age and those who underwent the index procedure at a hospital outside the United States. Medicare advantage beneficiaries, who are included in MedPAR files but have incomplete capture of health care claims, 12 were also excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%